2012
DOI: 10.1007/s11552-012-9420-6
|View full text |Cite
|
Sign up to set email alerts
|

The importance of pronator quadratus repair in the treatment of distal radius fractures with volar plating

Abstract: Background Open reduction internal fixation (ORIF) of distal radius fractures via a volar approach involves surgical release of the overlying pronator quadratus (PQ) muscle. Complete repair of the PQ, defined as full and stable replacement of the periphery of the PQ back to its original anatomic location, is not always possible upon conclusion of the operation. Postoperative consequences of incomplete PQ repair with regards to range of motion (ROM), grip strength, and complications are not well documented. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 16 publications
3
45
2
3
Order By: Relevance
“…Changes in the forearm position change kinetics and muscle activities, which largely determine the strength and stamina of power grips 5 , 21 , 35 . In accord with previous studies, 25 , 36 , 37 the average grip strength in the healthy adults in this study was greatest at the neutral position.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Changes in the forearm position change kinetics and muscle activities, which largely determine the strength and stamina of power grips 5 , 21 , 35 . In accord with previous studies, 25 , 36 , 37 the average grip strength in the healthy adults in this study was greatest at the neutral position.…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, biomechanical studies 3 , 4 suggested that the pronator quadratus acts as a crucial distal radioulnar stabilizer rather than a prime agonist for forearm pronation, which indicates that the pronator quadratus is an important contributor to forceful gripping effort 2 . In fact, several clinical studies 5 7 reported that the volar approach through detachment of the pronator quadratus or the degree of pronator quadratus injury did not affect pronation and grip strength. This conflicting information has led to the disparity related to the true function of the pronator quadratus muscles involved in gripping and forearm rotation 2 .…”
mentioning
confidence: 99%
“…19 Tosti and Ilyas 20 prospectively assigned 60 patients to repair or no repair, and found no improvement in postoperative range of motion, grip strength, reoperation rate, DASH score, or visual analog scale (VAS) score at 1 yr. Reapproximation of the PQ during closure is controversial.…”
Section: Pronator Quadratus Repairmentioning
confidence: 99%
“…Two retrospective studies and one prospective study analyzed the outcome after volar plating for distal radius fractures. 17,32,39 Four clinical studies directly analyzed the relation between volar plates and flexor tendons. 11,33,46 Four publications were expert opinions on the anatomy of the distal radius or volar plating of distal radius fractures.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In general, after comparing all descriptions, "the watershed line" could be divided into the following categories: (1) interpretations that are based on soft tissue landmarks 22,[30][31][32][33] and (2) interpretations using bony landmarks as the main anatomic reference. 11,17,[19][20][21]23,24,[26][27][28][34][35][36][37][38][39][40][41] Within these two categories, we found eight different interpretations of the term "watershed line."…”
Section: Study Characteristicsmentioning
confidence: 99%